Renal Doppler Index and its Correlation with Laboratory Index of Human Immunodeficiency Virus (HIV) Sero - Positive Adult Individuals - Andre Gunawan (Journal of Global Research in Public Health, 2022)
Renal Doppler resistive index (RI) and pulsatility index (PI) values ​​have the potential to be more sensitive in detecting kidney abnormalities when compared with standard laboratory indices in HIV/AIDS patients. To our knowledge, there are no published research articles on renal Doppler indices and their correlation with laboratory indices of HIV sero-positive adults. This study aimed to assess the renal function of HIV-positive adults using RI and PI, and correlate these indices with laboratory values. A prospective cross-sectional study was conducted from July 2019 to April 2020. A purposive sampling method was used and involved 396 HIV sero-positive adults. Sampling for renal RI and PI was performed at the level of the inter-lober arteries, between the medullary pyramids. RI values ​​above 0.70 and PI values ​​above 1.56 are considered abnormal. Serum creatine and urea together with evidence of proteinuria were noted at the time of scanning. Forty-three (10.9%) men had abnormal RI, 32 (8.1%) had abnormal PI, five (2.5%) had abnormal creatinine, two (1%) abnormal urea and eight (4.1%) ) with proteinuria. In women, 29 (7.3%) had abnormal RI, 22 (5.6%) abnormal PI, four (2%) abnormal creatinine and urea and six (3%) had proteinuria. There was a statistically significant weak positive correlation between RI and PI and serum creatinine and urea (r > 0.2, P < 0.05). The proportion of patients with abnormal RI and PI was higher than the proportion of patients with abnormal serum urea, creatinine and proteinuria. The renal Doppler index can be used for initial assessment of renal function in HIV sero-positive adults.